Critical Success Factors in the Business of Seed Industry Organizations - Petrović, Goran (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2020)
The goals of business systems stem from their mission and vision, and in order for an organization to be successful in achieving its goals, it is necessary to monitor (measure) performance and manage its performance. However, without defining the Critical Success Factors (CSF) of the business and then defining the appropriate indicators, it is not possible to properly manage performance. Critical success factors relate to certain key areas where everything has to be done well, since positive results in these areas occur as a condition of achieving the organization's goals. Critical success factors are specific to particular areas (branches of business), and the specificities of the organizations within one industry are generally reflected in unique sets of identified CSFs. The aim of this paper is to establish a methodological framework for identifying and solely identifying critical success factors in the seed industry, which, because of its specificity, is characterized by a high degree of uncertainty, despite being well-managed and controlled administratively. The paper outlines the critical success factors that affect the performance of an organization as a whole and its business processes and are essential to achieving the organization's goals in the seed industry and fulfilling its mission. The offered framework for determining the CSF as well as the set of proposed CSF organizations in the seed industry is based on a study of the relevant literature available as well as the results of a survey conducted with experts in the seed industry. Given the evident lack of appropriate scientific and professional literature that discusses the topic of performance management of business systems in this segment of agriculture, this paper makes an original contribution to the development of theory and practice of performance management in a specific field of seed industry.